WORK STRESS MANAGEMENT AND WORK MOTIVATION IN ISLAMIC PERSPECTIVE - Luthfi, Atabik; Syahrullah, Syahrullah; Hardjadinata, Hardjadinata; Edi, Deden; Putra, Fajar Harguna Endra (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Work stress and work motivation are two factors that greatly influence individual performance in the work environment. From an Islamic perspective, work stress can be managed through a spiritual approach, such as tawakal, sabar, and sholat, which function as coping mechanisms to overcome work pressure. Meanwhile, work motivation in Islam is not only oriented towards material things but also on the intention to seek Allah's pleasure (ikhlas) and work as a form of worship. This study aims to analyze the concept of work stress management and work motivation from an Islamic perspective and how to implement it in professional life. The research method used is library research by analyzing Islamic literature, including the Qur'an, Hadith, and the views of related scholars. The results of the study indicate that work stress management in Islam emphasizes a balance between worldly endeavors and spirituality, such as maintaining physical and mental health and strengthening relationships with Allah. Meanwhile, work motivation based on Islamic values ​​can improve work ethic and more meaningful job satisfaction. The application of stress management and work motivation from an Islamic perspective can be an effective solution in creating a healthy and productive work environment.